Analisis Stabilitas Lereng Menggunakan Slope/W Pada Area Gudang Semen Pongkor - Paula Valery Dorothy; Asriwiyanti Desiani; Cindarto Lie (Jurnal Teknik Sipil, 2026)
This study was conducted to analyze the slope stability around the Semen Pongkor Warehouse area in Bogor Regency. Initial inspections revealed significant structural deformation in the warehouse building, indicating potential slope instability. Geotechnical investigations were carried out through core drilling up to a maximum depth of 30 meters, Standard Penetration Test (SPT), and laboratory testing of undisturbed soil samples. The data obtained from these investigations were used to evaluate the slope’s factor of safety (FoS) through modeling with GeoStudio SLOPE/W software. The results showed that the existing condition had a Factor of Safety (FoS) of 1.23 (FoS < 1.5). Therefore, a new model was developed with the addition of soldier piles (60 cm diameter, 35 m length) and soil nailing (20 cm diameter, 35 m length). After implementing these reinforcement measures, the FoS increased to 1.503, which fell within the safe range (FoS ≥ 1.5). These findings highlight the importance of continuous monitoring and maintenance by installing instruments such as inclinometers and piezometers to monitor slope deformation and prevent potential landslides.